Body image in women diagnosed with breast cancer: A grounded theory study. (June 2022) - Brunet, Jennifer; Price, Jenson; Harris, Cheryl
Abstract: Using a Straussian grounded theory methodology, we explored the meaning women attribute to body image and how they understand their breast cancer experience as influencing their body image to develop a grounded theory of body image for women diagnosed with breast cancer. Interviews were conducted with 27 women who had completed treatment for breast cancer in Canada. Data were analyzed through a process of open, axial, and selective coding using constant comparison techniques and memo-writing. A grounded theory of body image for women diagnosed with breast cancer was developed around the core category of body image: what it means to women, which was underpinned by six themes and 17 subthemes. This theory explains how women diagnosed with breast cancer define body image and illustrates intrapersonal and interpersonal factors that can undermine or support their body image, along with strategies they used to manage their body image. This theory can guide research and practice aimed at enhancing body image and minimizing its consequences for women diagnosed with breast cancer. Highlights: Body image may change among women following a breast cancer diagnosis. A lack of body image theories impedes knowledge development to guide practice. Treatment-related and psychosocial factors may undermine or support body image. Sociocultural factors may undermine body image. Passage of time and various strategies may help women manage their body image.